Trump Threatens Military Action in Nigeria: Musings on his Real Intentions: CODESRIA Bulletin Online, No. 12, November 2025 - Yusuf Bangura, (CODESRIA Bulletin, 2025)
The widely circulated article in Global Geopolitics (2 November 2025), ‘America’s Hypocrisy as Policy’, offers a thoughtful reaction to US President Donald Trump’s insane but self-serving threat to invade Nigeria under the pretext of stopping a so-called Christian genocide. Trump tweeted on 31 October and 1 November 2025 that ‘Christianity is facing an existential threat in Nigeria’, named Nigeria as ‘a Country of Particular Concern’, and announced that the US was ‘ready, willing and able to save our Great Christian population around the World’. He also ordered the military to prepare to intervene in Nigeria and boasted that ‘if we attack, it will be fast, vicious and sweet’ (Winter 2025). Trump has often been described as a narcissist—someone who is deeply self-infatuated and impulsively seeks attention and adulation. Earlier this year, John MacArthur (2025), the publisher of Harper’s Magazine, writing in The Guardian, described him instead as a solipsist—a word he borrowed from the investigative psychiatrist Robert Lifton. A solipsist is someone who makes no attempt to court or please others, since the only point of reference is himself. Solipsists revel in making outrageous statements because they love being attacked to draw attention to themselves. It is easy to dismiss Trump’s inflamed anti-Nigeria rhetoric as the rants of a narcissist or solipsist, since anyone who is familiar with Nigeria knows that the violence in that country affects both Christians and Muslims. ‘He cannot be serious’, some have argued. However, his insanity or wild outbursts may not be without material foundation. Trump often follows through on his rants if he does not face stiff resistance—especially when his anger is directed at groups, individuals or institutions he considers weak. There are always interests and a method in his madness or egotistical rants. As the Global Geopolitics article notes, Nigeria is located within a resource-rich region that is important to the supply chains of US hi-tech companies and defence industries. That region stretches from Nigeria through Niger and Chad to Sudan and is endowed with vast amounts of rare earth minerals. Apart from oil, Nigeria has enormous reserves of lithium, cobalt, nickel and other rare earths, which are embedded in solid rock and heavy mineral sands. It is ranked fifth globally in the production of rare earth elements (US Geological Survey, 2025)—behind China, the US, Myanmar and Australia. Segun Adeyemi (2025) recently reported in Business Insider Africa that Chinese companies have invested more than USD 1.3 billion in Nigeria’s fast-growing lithium-processing industry. Combined with the leverage that Russia now wields in the mineral-rich Sahel states of Niger, Burkina Faso and Mali, China’s growing economic influence in West Africa’s regional power, Nigeria, should be of serious concern to the US, since China already dominates the global rare earths industry. The US has been strategising about how to end its high level of dependence on China for rare earths, which are essential for clean energy, such as electric vehicles, solar panels and wind turbines, and in electronic consumer products, such as LED television screens, computers and smart phones. These minerals are also required to produce jet engines, missile guidance and defence systems, satellites and GPS equipment. After threatening China with a 140 per cent tariff when China imposed restrictions on the global supply of rare earths, Trump quickly made a U-turn in his recent meeting with China’s president, Xi. He realised that a trade war with China on rare earths would profoundly hurt the US economy. Under the deal he struck with Xi, Trump agreed to end the tariff threat and lift the ban on Chinese companies’ access to US chips, while Xi agreed to restart China’s supply of rare earths and purchase US soyabeans for one year (Krugman 2025). Trump praised Xi as a great leader when he returned to the US. The US is in panic mode in the geopolitics of rare earths trade. On his recent visit to Southeast Asia, Trump signed a raft of agreements with several countries in the region to beef up the production and processing of rare earths and exports to the US (CSIS 2025). Various reports by experts in geopolitics (Roy 2025; Indian Council of World Affairs 2025) indicate that the Trump administration sees Africa as an important source of critical minerals that will help wean the US off China. The administration brokered a peace deal between the Democratic Republic of Congo (DRC) and Rwanda in June 2025, which included an investment agreement that allows the US to invest in DRC’s minerals. Deals with other countries, such as Kenya, Tanzania, Angola, Malawi and Namibia are being discussed or supported. In 2022, the US and other Western countries launched a fourteen-member minerals security partnership (MSP) to boost the production and supply of critical minerals that will benefit member states. The MSP works with the multilateral financial institutions and export credit agencies to provide finance for specific projects. It holds forums with a number of countries that produce rare earths, including the DRC, Botswana and Zambia (US Department of State, n.d.). US interests are not driven by humanitarian concerns The history of the US’s quest for foreign resources indicates that it uses multiple strategies, such as coercion, war, bribery and diplomacy, to achieve its goals. Coercion involves suspending aid or other economic benefits and political support to compel an adversary to bend to the will of the US. When Trump suspended the US’s aid programme and declared a trade war with the rest of the world in April 2025, several African and other leaders rushed to make deals with him. Global Witness (2025) revealed, in July 2025, that seventeen countries (including six from Africa—viz Angola, DRC, Liberia, Mozambique, Rwanda and Somalia) have hired Trump loyalists as lobbyists to help broker deals, ‘with many bartering key resources including minerals in exchange for humanitarian or military support’. The use of war to pursue US strategic and economic interests is well documented in the field of geopolitics and international political economy. During the Cold War, the US and other Western countries simply intervened in countries that threatened their vital interests without bothering to disguise their actions with lofty humanitarian objectives. One of the most famous cases was the US invasion of Guatemala in 1954 to stop the land reform programme by Jacobo Arbenz Guzman’s leftist government that threatened the land holdings of the United Fruit Company—a US multinational with considerable power and interests in Central America. The brazen Anglo-French invasion of Egypt in 1956 when Egypt nationalised the Suez Canal is another well-known case. Often, when US interests were threatened, rather than go to war US leaders relied on the CIA to work with local disaffected elements in the military to engineer a change of government or kill the incumbent president. The cases are overwhelming—such as the murder of Congo’s Patrice Lumumba in 1961 and Salvador Allende of Chile in 1973, and the overthrow of Mohammed Mossadegh of Iran in 1953. All these countries had huge mineral resources. The rationale used by the US and its Western allies for invading countries changed when the Cold War ended in the 1990s and the US emerged as the sole superpower. The concept of humanitarian intervention gained ground within the United Nations system. This involved the US and other Western powers working through the UN to end wars and rebuild war-battered societies. During that period, the US felt it did not face any existential threat, like communism, and could act as a moral force or policeman of the world while hiding its real interests. That posture rhymed with the values of the unipolar world: the spread of democracy, human rights and economic or market liberalism. The US, however, faced strong resistance from most countries when it tried to use humanitarianism to overthrow governments it did not like without evidence to support its claims. Matters came to a head in 2003 over Iraq, which the US invaded under the humanitarian pretext of disarming it of weapons of mass destruction. It turned out that there were no such weapons. The US was simply after Iraq’s oil and helping to dismember a formidable foe of Israel. As the Global Geopolitics article demonstrates, US interventions under the pretext of humanitarianism have always been catastrophic for those who live in the affected countries. After the old regime has been dislodged, the US often leaves the shattered countries to sort out the mess while it retains control of the resources that are the hidden but real reason for the interventions. Nigeria’s violence has multiple dimensions Numerous reports and studies have shown that Nigeria’s violence affects Christians and Muslims (Ibrahim 2024, 2025; Amnesty International 2025; Okoli and Atelhe 2014). No group is insulated from it. I can think of six types of violence in the country. The first three are the Boko Haram, Islamist-inspired violence in the Northeast, whose main victims are Muslims who reject the group’s Islamist ideology; banditry in the Northwest, which affects Muslims and Christians in equal measure; and the ‘herder-farmer’ conflict in the Middle Belt, which affects Christians and Muslims, although reports indicate that Christians are the main victims of that violence. The other three types of violence are the ‘herder-farmer’ violence in the Northwest, in which Fulani herders are reportedly pitched against Hausa farmers (both groups are Muslim); the violence inflicted by the Indigenous People of Biafra and bandits in the East against their own people, Igbos, who are Christian; and general banditry in large parts of the country, which has rendered travelling by road between cities risky. The Nigerian state has been terribly negligent in its duty to protect the lives of Nigerians. And its poor record of economic management, corruption and poverty has driven many people to the edge. However, as can be seen from the above review, the state itself is not the key actor generating the violence. Non-state actors actively drive it. If Christians and Muslims are equally affected by Nigeria’s multilayered violence, how did the narrative of Christian genocide emerge? A narrative of Christian genocide and Fulanisation has been developing among some groups in Nigeria who feel helpless as raw terror takes hold of their lives and communities, especially during the administration of Muhammadu Buhari, a Fulani, who was accused of being soft on Fulani herders when they committed wanton atrocities against other ethnic communities in the Middle Belt. That narrative feeds into Nigeria’s often toxic ethnic and religious discourse on domination and marginalisation. Lately, some of these groups have intensified their narrative to win support from powerful Western constituencies. These groups have mastered the techniques of misinformation through various social media outlets, networking and lobbying to insert their grievances into the politics of far-right movements in the US. Having a president like Trump who thrives on culture wars is seen as a boon. White far-right groups in South Africa provided the road map. When, in February 2025, Trump accused the South African government of genocide against white farmers and condemned that country’s new land ownership law as racist, it was the post-apartheid discourse of white victimhood and lobbying activities of a right-wing Afrikaner pressure group, AfriForum, that got the Christian Right in the US, Republican policymakers and Trump to adopt the narrative of white genocide. Some disaffected groups in Nigeria have copied from the playbook of AfriForum by drumming up the rhetoric of Christian genocide. Phillip van Niekerk (2025) reports in the Daily Maverick that diaspora ‘Biafran separatists’ have ‘repackaged their secessionist grievance as a struggle to save “persecuted Christians”’ and have been engaged in a lobbying campaign in Washington in partnership with Mercury Public Affairs, BW Global Group and Daniel Golden. There is also a video circulating on WhatsApp, which shows a Catholic Bishop of Makurdi Diocese in Benue State in Nigeria, Wilfred Anagbe, addressing an audience in the US, in which he paints a dire picture of the fate of Nigerian Christians, alleging that Nigeria is being turned into an Islamic state and Christians are being wiped out. And in a letter signed by the president and vice president of the American Veterans of Igbo Descent to Trump, the organisation declared that they ‘are ready and willing to assist in any efforts aimed at the liberation and protection of Christians in Nigeria’ (Onyia and Obiagwu 2025). These campaigns have resonated with American Christian nationalists, whose politics is driven by the notion of Christian civilisation under siege and the imperative of defending it. Hard-right politicians in the Republican Party, such as Ted Cruz, conservative political commentator, Bill Maher, Black corporate democrats and corporate journalists, such as New York City Mayor Eric Adams and Van Jones, and many others in Trump’s MAGA base, have jumped on the bandwagon. Cruz introduced a bill in the US Senate in September 2025 that designated Nigeria as a Country of Particular Concern and imposed sanctions on Nigerian officials who are perceived as facilitating ‘Islamist jihadist violence’ and blasphemy laws (Cruz 2025). Does Trump have a beef with Tinubu? Why didn’t Trump try to discuss his alleged grievances with Tinubu instead of threatening him with war? Where a vassal relationship exists between a great power and a weak state, recourse to war is never the first option in making demands. The great power can use various methods, including coercion, to get the vassal state to do its bidding. This is what Trump has done in Ukraine and the DRC. He has been able to gain access to the mineral wealth of those two countries without declaring war on them. Recent developments suggest that relations between Trump and Tinubu may not be that cordial. Trump has been unable to get Tinubu and his government to support several of his pet projects in the foreign policy field. We could start with the Niger-ECOWAS conflict, which Trump inherited from Biden. Just after taking office in 2023, Tinubu gave the impression in the eyes of many that he had signed up to the project of policing the West African region on behalf of Western interests. As Chair of the Economic Community of West African States (ECOWAS), he issued an ultimatum to the military leader of Niger, General Abdourahamane Tchiani, who had staged a coup, to hand power back to the deposed leader, Mohammed Bazoum or face military intervention. Some of the most draconian sanctions in Africa were imposed on Niger, including cutting off the electricity supply and trade relations, and blocking financial transactions between ECOWAS and Niger (Bangura 2025a). It seemed that Tinubu, who had just won a highly disputed election and seemed unaware of Nigeria’s core strategic interests, was being egged on by Alhasan Ouattara of Côte D’Ivoire and Macky Sall of Senegal—both regarded as client leaders of the French president, Emmanuel Macron—to reverse the coup in Niger by military force. France, supported by the EU and the US, was not willing to lose control of Niger’s rich deposits of uranium and its military base. The US was also worried about its drone base in the south of Niger, which served as part of its counterterrorism activities. However, Tinubu faced significant opposition from Nigerians, especially Northern clerics, civil society activists and the National Assembly. He huffed and puffed but failed to pull the trigger. His abrupt climb down bolstered the confidence of the military leaders of Niger, Burkina Faso and Mali to withdraw from ECOWAS, which they described as a neocolonial instrument of Western powers; they formed an alternative organisation—the Alliance of Sahel States. The failure of ECOWAS under Tinubu to reverse Niger’s military coup may have convinced Trump that he could not be relied on to carry out the West’s agenda in West Africa, even though he continues to maintain cordial relations with Macron in France (Bangura 2025b). The US may also have faced a rebuff from the Tinubu administration to relocate its Niger base to Nigeria when Niger’s military leader ordered the US to shut down its base in Niger. Civil society activists raised the alarm that there were active discussions between the US and the Tinubu administration to relocate the base to Nigeria (Mohammed 2024). Growing opposition to the idea forced the US and Nigerian authorities to deny the allegations. Two other areas of conflict are worth highlighting to underscore the strained relations between Trump and Tinubu. The first is Nigeria’s emphatic rejection of Trump’s request to accept Venezuelan deportees or third-party prisoners from the US. Adding insult to injury, Tinubu’s foreign minister, Yusuf Tuggar, evoked a famous remark from the US rap group Public Enemy in rejecting the request: ‘In the words of the famous US rap group Public Enemy … You’ll remember a line from Flav Flav—a member of the group—who said: Flav Flav has problems of his own. I cannot do nothin’ for you man’ (Akínpẹ̀lú and Booty 2025). This must have rankled Trump, especially as other African countries, such as Ghana, Rwanda, Eswatini, South Sudan and Uganda, had agreed to accept his deportees. It is important to note that Trump has a dystopian view of Africa, which he described during his first term in office as a continent of ‘shithole countries’. John McDermott (2025), The Economist’s Chief Africa correspondent, highlighted this week in his column comments made by Trump about Africa on Air Force One, which reveal his ‘generally apocalyptic assumptions about Africa’: ‘[In Africa] They have other countries, very bad also, you know that part of the world, very bad …’. With these kinds of views, Trump would not expect an African leader to turn down his request for help. Such a leader should be taught a lesson, he would imagine. Then there is Nigeria’s decision to stick to its longstanding policy of supporting a two-state solution to the Israel-Palestine conflict. Tinubu’s foreign minister, Tuggar, has also been clear and forthright in condemning Israel’s genocidal carnage in Gaza. He described the violence as ‘something every human being should stand up and oppose’ (Durosinmi 2025). Nigeria was part of 119 states that voted for immediate ceasefire in Gaza when the violence first erupted in 2023. It also voted, in 2024, against Israel’s occupation of Gaza. So, what we have is a confluence of interests—local and foreign, and economic and ethnoreligious—as well as personal grievances and a warped view of Africa that have shaped Trump’s decision to threaten military action in Nigeria. However, no great power threatens war to save the souls of foreign people it despises or with whom it shares no strong bonds. History suggests that lurking behind every US intervention is the pursuit of economic and geopolitical interests. I have tried to imagine what the US would do if it were to carry out its military threat. Would it bomb the Tinubu government out of existence, which would lead it to confront the real terror groups? Or would it ignore the Tinubu government and conduct a bombing campaign against the terrorists, who operate clandestinely in small groups? Either way, the US would be involved in a messy and costly guerrilla war that it will have no stomach to fight. It is important to note that the US has never been successful in defeating terrorist groups in their own countries. It lacks the zeal, commitment and technique to sustain a long-drawn-out war. The US history of intervention to save humanity is littered with abject failures: Iraq, Libya, Syria, Afghanistan and Somalia hold sobering lessons. However, the chaos of intervention may not prevent the US from trying to control Nigeria’s rich resources. Mining companies have a reputation of thriving in conflict zones by striking deals with local militias. Conclusion Tinubu has released a press statement in which he highlighted his government’s policy of engagement with Christian and Muslim leaders since 2023, to address security challenges that affect ‘citizens across faiths and regions’. He affirmed that Nigeria is not a religiously intolerant country and opposes ‘religious persecution’. He has followed this up with a twenty-four-page document on ‘Nigeria and Religious Persecution: Deconstructing a Linear Narrative’, prepared by the Office of the Minister of Foreign Affairs (2025), which challenges in substantial depth the narrative of a Christian genocide. However, Tinubu’s conclusion in his press release that his ‘administration is committed to working with the United States government and the international community to deepen understanding and cooperation on protection of communities of all faiths’ has raised eyebrows. Could this be what Trump really wants to achieve with his military threat? Get the Tinubu administration to open talks with the US, which will then try to introduce the issue of rare earths and other economic and strategic issues in the negotiations, and force a deal?